MECHANISM OF INCOME TAXATION OF INDIVIDUAL PERSONS - Yangiboev H. A. (Scholars Digest Publishing, 2023)
In this article, the fundamentals of the introduction of personal income tax, its economic significance, the opinions and comments of economists regarding its implementation, the essence of personal income tax, the single rate collection of personal income tax in the Republic of Uzbekistan from January 1, 2019, as a result, the increase of monthly wages was analyzed and conclusions and proposals for improvement were developed.